“You Don’t Know Me so Don’t Try to Judge Me”: Gender and Identity Performance on Social Media Among Young Indian Users - Majumdar, Sramana; Tewatia, Maanya; Jamkhedkar, Devika; Bhatia, Khushi (Frontiers in Psychology, 2022)
Social media is the preferred communication platform for today’s youth, yet little is known of how online intergender communication is shaped by social identity norms. Drawing from the Social Identity and Deindividuation Effects (SIDE) approach, we argue that through depersonalization, online interactions are marked by the salience of social identities and identity performance conforming to perceived norms of behavior (traditional as well as developing). We specifically look at discursive terms and their meaning-making as a strategic performance of gender in uncontrolled social media interactions. We examined a corpus of 442 comments from selected public Indian Facebook pages in two phases over a span of one year (2020-2021). Thematic discourse analysis revealed established (#mansplaining, pseudofeminism) and emerging (choice feminism, MGTOW, #fuckboi etc) discursive strategies within the major themes on feminism and antifeminism, men’s rights, intersectional feminism, and sexual behavior. These meaningful terms are used to modulate identity performance in a heavily contested space, reflecting both consolidation as well mobilization functions, as proposed by SIDE. The findings highlight that intergender communication on social media is both dependent on existing offline norms, while challenging the same to create new discourses of gender. Keywords: Social media, Social identity, SIDE, CMC, Gender, Feminism